PENGARUH PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP HASIL BELAJAR SISWA KELAS II PADA MATA PELAJARAN FIQIH DI MI AL – IKHLAS CICADAS BOGOR - Anugrah Suci Prihatini; Syarifah Gustiawati Gustiawati; Sutisna Sutisna (KOLONI, 2022)
The Picture and Picture learning model in the learning process emphasizes that students are required to be responsible for everything that is done in their group. This study aims to determine the effect of the application of the Picture And Picture model on the learning outcomes of class II students in fiqh subjects at MI Al - Ikhlas Cicadas Bogor. The approach used in this study is a quantitative approach with a true experimental design type of research. This study aims to answer questions in the formulation of the problem which include: 1) How is the application of the Picture And Picture learning model to the learning outcomes of class II students in the control and experimental classes at MI Al – Ikhlas Cicadas Bogor 2) How are the learning outcomes of class II students in the experimental class on the subject of fiqh by using the Picture And Picture learning model at MI Al – Ikhlas 3) How does the Picture And Picture learning model affect the learning outcomes of class II students in the experimental class at MI Al – Ikhlas Cicadas Bogor. The results of this study indicate that: a) the application of the Picture And Picture learning model in the experimental class most students are able to think logically, this is evidenced by the ability of students to compose pictures of the material that has been studied, which of these activities train the level of students' thinking abilities and students are more enthusiastic, active and enthusiastic because the learning process with pictures attracts students' attention more b) learning outcomes on the average pretest score of students in the control class is 33.77 and the pretest of students in the experimental class is 59.64 , meanwhile the results of the average value in the posttest control class is 69.11 and the posttest in the experimental class is 78.58 c) the effect of the significance of the difference in the average of the two groups given the treatment of both the conventional model and Picture And Picture which is applied to the Mann test -Whitney obtained Asymp results. Sig. (2-tailed) 0.029 < 0.05. So it can be concluded that there is a significant effect between the Picture and Picture model on learning outcomes in fiqh subjects with a medium significance category because the significance value used by researchers is 0.05 (5%). The Picture And Picture learning model can be used as an alternative for teachers in the fiqh learning process in order to develop a learning model that is applied to students, so that students do not feel bored when carrying out learning activities, this saturation can be minimized optimally, with the implementation of the Picture And Picture learning model in the learning process. the learning process to determine the effect on students' cognitive learning outcomes to contribute optimally in the learning process.  Keywords: Learning Outcomes, Picture And Picture, Fiqh.